Nickel‐Catalyzed Four‐Component Carbonylation of Ethers and Olefins: Direct Access to γ‐Oxy Esters and Amides. (5th July 2022) - Wang, Le‐Cheng; Chen, Bo; Zhang, Youcan; Wu, Xiao‐Feng
Abstract: Multi‐component carbonylation of olefins, a reaction that installs both a carbon–carbon(heteroatom) bond and a carbonyl group across the double bond, is an attractive strategy for alkene functionalization. Herein, we developed a novel nickel‐catalyzed four‐component carbonylation of olefins with ethers under low CO gas pressure. Using alcohols and amines as the reaction partner, diverse γ ‐oxy‐substituted esters and amides were produced in good yields with excellent functional group tolerance. Notably, Naftidrofuryl, a medicine for the treatment of cerebrovascular disease (CVD), can be synthesized by this process straightforwardly. Abstract : A new nickel‐catalyzed four‐component carbonylation of ethers with olefins to synthesize γ ‐substituted carbonyl compounds has been developed. A variety of γ ‐substituted carbonyl compounds were produced in excellent yields under 1 atm pressure of CO. Notably, this strategy has been successfully applied to the one‐step synthesis of the drug molecule Naftidrofuryl, which is a medicine for the treatment of cerebrovascular disease (CVD).